Pendampingan Pembelajaran Bahasa Inggris Dasar Pada Eks-TKI Di Dusun Sumberwaru Desa Tamanagung Kecamatan Cluring Kabupaten Banyuwangi - Lestari, Sutami Dwi (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2019)
English is an international language that is used as the language of world communication. Indonesian migrant workers and eks-migrant workers need the ability to communicate in English because it can affect their level of success while working in other countries. This community service activity aims to provide basic English language learning assistance to eks-TKI in sub village of Sumberwaru village, Tamanagung sub-district, Cluring, Bbanyuwangi district which is 30 kilometers from the center of the district administration. The training was attended by 12 people with four face-to-face meetings each with a duration of 2 hours. Face-to-face meetings are conducted with lecture and demonstration methods, followed by practice / practice. The subject presented was divided into three discussion materials, namely Part of speech, Tenses, and Sentences. The obstacles faced in the activity were relatively short training times and varied material capture of the participants. In general, this activity went well and received enthusiastic welcome from the participants who participated in the training completely.